Top managers' attributes, innovation, and the participation in China–Pakistan Economic Corridor: A study of energy sector small and medium-sized enterprises - Syed Zulfiqar Ali Shah; Muhammad Anwar; Ch. Mazhar Hussain (Managerial and Decision Economics, 2020)
A large number of researchers are engaged in studying the determinants and consequences of China–Pakistan Economic Corridor (CPEC). Although optimism abounds, in particular, few empirical evidence is available for Pakistani businessmen and small and medium-sized enterprise (SME) operators on how to benefit from this tremendous opportunity. Our study examined how top managers/owners of Pakistani energy sector SMEs can innovate their businesses to reap the benefits of CPEC. We have examined the influence of demographic factors (age, education, experience, and financial literacy) of top managers/owners on different forms of innovation (product, process, marketing, and organization) and their consequent chances of success through participation in CPEC.
Keywords: 650